PENGARUH KEPEMIMPINAN ISLAMI TERHADAP MOTIVASI, KINERJA, SERTA KESEJAHTERAAN ISLAMI - A'rasy Fahrullah (al-Uqud : Journal of Islamic Economics, 2018)
This study aims to examine and analyze the influence of Islamic Leadership on Work Motivation, Islamic Performance, and Welfare of Islamic Hospital Employees in Tulungagung Regency. The unit of analysis in this study is the employees of Islamic Hospital or Islamic nuanced hospitals in Tulungagung. While population in this research are employees of Islamic hospitals in Tulungagung District, and sampledby 133 people. Methods of research using quantitative structural equation models with AMOS software. The results can be summarized as follows: Islamic leadership influences employee motivation in Islamic hospitals. Islamic Leadership affects the performance of Islamic Hospital employees. Islamic leadership affects the welfare of employees in Islamic hospitals. Working motivation affects the performance of employees of Islam Hospital. But the motivation and performance did not effect significantly to the employee welfare at the Islamic hospital in Tulungagung.